Pengaruh Desa Wisata Candriejo Terhadap Fungsi Lahan, Ekonomi dan Pelestarian Budaya - Ferry Oloan Nadeak; Muhammad Muktiali (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Trends and travel has experienced a shift from the conventional nature of particular interest one rural tourism. Rural tourism pattern forming an emotional connection between the tourists with the place and the people who visit. Rural tourism offers activities that were able to spend leisure travelers with the activities of natural and condensed with the culture of the people. One form of rural tourism development, namely the Tourism Village. Candirejo Tourism Village is one of the tourist village located in the district of Magelang located around the Borobudur Temple. Tourist village offers a natural tourist attraction with packaging Javanese cultural nuances are very typical. The daily activities of the villagers, planting paddy fields, cooking in the kitchen, became gamelan and traditional arts as a dancer trian will provide a special experience for every tourist who comes. The existence of the Tourism Village Candirejo certainly an impact on the physical and non-physical. The physical aspects such as land use change and non-physical aspects such as economy and culture in the community. This study aims to determine the effect of the Tourism Village Candirejo land use, economic and cultural preservation.